Pendidikan Politik bagi Perempuan - Syarifah Rahmah (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2021)
Women who are represented in the Regency/City DPRD have not yet reached the 30% quota as mandated by the law. The number of women's representation proves that the mandate of the law has not been carried out as it should. The aspirations of women in their political activities are still not respected, there are still many policies that are made that are still biased, women are considered not capable of entering the political sphere, men who should be included in the political arena are men. Many political parties in Indonesia have not accommodated women's rights, especially providing political education to women. Whereas the mandate of the law requires every political party, both national political parties and local parties in several provinces in Indonesia. However, the next obstacle that arises is the understanding of culture that is difficult to overhaul in the social order, some people still hold the principle of patriarchy in which the subordination of men is more dominant than women, so that the capacity of women who want to exist in the political field is hindered. Weaknesses and responsibilities of women in the family sphere are used as reasons to marginalize women's political rights. The biggest homework for the Indonesian people is to raise awareness to the people who are still bound by the cultural system that men and women have the same qualities to assume positions as leaders.